Strategi Brand Positioning Berbasis Keberlanjutan Lingkungan: Studi Kasus Napak Bhumi 2021-2024 - Bianca Rayhanna Ramadhanti Moksen; Kayla Ratna Zahra Suradimaja; Jefri Audi Wempi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
The fashion industry significantly impacts the environment, especially through textile waste from fast fashion. In 2021, Indonesia produced around 2.3 million tons of textile waste. This study explores the sustainability strategy of Napak Bhumi. This local brand transforms textile waste into eco-friendly shoes, uses traditional packaging, supports local artisans, and donates 10% of profits to underprivileged children through the #Tinggalkanjejakbaikmu campaign. Using qualitative methods interviews with five sources and social media analysis the findings show consumers value sustainability beyond product design. This reflects a growing awareness among young generations and offers key insights for brands aiming to integrate social and environmental values into their marketing strategies.